(untitled) (Damascus University Journal of educational and Psychologyical sciences, 2025)
The aim of the research was to determine the attitudes of the faculty members at the College of Education towards the use of artificial intelligence applications in scientific research, and to identify the significant differences in their attitudes based on the variables of academic rank and scientific department. The research adopted a descriptive-analytical approach, and the study sample consisted of (128) faculty members at the College of Education, University of Damascus, A survey on attitudes towards the use of artificial intelligence applications in scientific research, consisting of (44) items distributed into four domains prepared by the researcher. The study results showed that the attitudes of the faculty members at the College of Education towards the use of artificial intelligence applications in scientific research were of moderate degree for all dimensions and the survey as a whole, Additionally, the results indicated that there were no statistically significant differences in the attitudes of the faculty members based on the variables of academic rank and scientific department. Based on these findings, the research presented a set of recommendations and proposals.